Sosialisasi Penerapan Teknik Menyimpan pada Materi Pengurangan Untuk Bilangan 20-100 di Sekolah Dasar - Zulvia Misykah -; Dinda Widyastika; Dewi Sartika Panggabean; Muhammad Dekar Nasution; Bulan Nuri (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Mathematics is a learning material at the level of education that cannot be separated from human life activities, both personal activities and social activities, personal activities such as the need to see the clock or cook cakes. While social activities such as buying and selling transactions where buyers and sellers must have the same ability in calculating addition and subtraction, integer subtraction operations have been taught since grade II in elementary school. However, during the learning process it is not as easy as imagined, there are things that hinder learning objectives from being achieved, such as material that is difficult to understand because the teacher's explanation does not reach the students. This requires teachers to be able to solve problems in class, so that the teacher's explanation can be understood by students, a technique is needed to teach subtraction material, this technique separates 1 number from a number which is then stored, and at the end of the subtraction process the number 1 will be added back. With the socialization of this storage technique, it is hoped that it will make it easier for students to learn subtraction material.